Childhood trauma and insulin-like growth factors in amniotic fluid: an exploratory analysis of 79 women - Lamadé, Eva; Hendlmeier, Ferdinand; Wudy, Stefan A.; Blum, Werner F.; Witt, Stephanie; Rietschel, Marcella; Coenen, Michaela; Gilles, Maria; Deuschle, Michael (Psychoneuroendocrinology, 2021)
Background - Perinatal stress has adverse effects on fetal outcome, yet the effect of early maternal trauma on fetal outcome has scarcely been studied. We investigated effects of maternal childhood trauma and current environment on important regulators of prenatal growth, fetal insulin-like growth factor (IGF)-1 and IGF-2 in amniotic fluid and assessed the impact of IGFs on newborn anthropometrics. - Methods - 79 pregnant women in their second trimester who underwent amniocentesis (15.9 ± 0.9 weeks of gestational age) and their newborns at birth were analyzed. Maternal childhood trauma was assessed using the childhood trauma questionnaire (CTQ) and current environment was operationalized by assessing maternal psychosocial, physical health and endocrine measurements in amniotic fluid. - Results - In this exploratory analysis of 79 pregnant women, maternal childhood trauma, defined as reporting at least low scores on any of the CTQ subscales, negatively correlated with fetal IGF-1 (Mln = 3.48 vs. 2.98; p = 0.012) and IGF-2 (Mdnln = 4.99 vs. 4.70; p = 0.002). Trauma severity, defined as the overall trauma score, negatively correlated with fetal IGF-2 (r = −0.24; p = 0.037). From trauma subscales, maternal sexual abuse correlated with fetal IGF-1 (r = −0.32; p = 0.006) and IGF-2 (r = −0.39; p = 0.001). Maternal BMI negatively correlated with fetal IGF-1 (r = −0.26; p = 0.023) and IGF-2 (r = −0.29; p = 0.011). Newborn anthropometrics were operationalized by length, weight, sex, gestational age, length/gestational age and weight/gestational age at birth. Fetal weight at birth associated with a trend with fetal IGF-1 when controlling for BMI. Maternal hypothalamus-pituitary-adrenal axis activity and maternal exercise did not contribute significantly to predicting fetal IGFs. Maternal childhood trauma (β = −0.27; p = 0.011) and BMI (β = −0.24; p = 0.026) remained significantly associated with fetal IGF-1. Maternal childhood trauma (β = −0.32; p = 0.003), maternal BMI (β = −0.30; p = 0.005) and maternal sexual abuse (β = −0.22; p = 0.049) remained significantly associated with fetal IGF-2 and with a trend with fetal IGF-1 (β = −0.21; p = 0.076) when excluding women with gestational diabetes. - Conclusion - Maternal childhood trauma and BMI associate negatively with fetal IGF-1 and IGF-2 in amniotic fluid. Controlling for maternal BMI, fetal weight at birth remains associated with a trend with fetal IGF-1. The presented data suggests that childhood trauma can affect endocrine measurements of the developing next generation, providing a mechanism by which adverse maternal life events are transmitted to the next generation.